ECT9 condensates with ECT1 and regulates plant immunity - Wang, Hui; Niu, Ruixia; Zhou, Yulu; Tang, Zhijuan; Xu, Guoyong; Zhou, Guilong (Frontiers in Plant Science, 2023)
Mounting an efficient defense against pathogens requires RNA binding proteins (RBPs) to regulate immune mRNAs transcription, splicing, export, translation, storage, and degradation. RBPs often have multiple family members, raising the question of how they coordinate to carry out diverse cellular functions. In this study, we demonstrate that EVOLUTIONARILY CONSERVED C-TERMINAL REGION 9 (ECT9), a member of the YTH protein family in Arabidopsis, can condensate with its homolog ECT1 to control immune responses. Among the 13 YTH family members screened, only ECT9 can form condensates that decrease after salicylic acid (SA) treatment. While ECT1 alone cannot form condensates, it can be recruited to ECT9 condensates in vivo and in vitro. Notably, the ect1/9 double mutant, but not the single mutant, exhibits heightened immune responses to the avirulent pathogen. Our findings suggest that co-condensation is a mechanism by which RBP family members confer redundant functions.